Identification and natural functions of cyclic lipopeptides from Bacillus amyloliquefaciens An6. Issue 5 (12th December 2016) - Ben Ayed, Hanen; Hmidet, Noomen; Béchet, Max; Jacques, Philippe; Nasri, Moncef
Abstract : Lipopeptides constitute a structurally diverse group of metabolites produced by various bacterial and fungal genera. In the past decades, research on lipopeptides has been fueled by their surfactant activities. However, natural functions of lipopeptides compounds have received considerably less attention. The aim of this study was to isolate and identify the lipopeptides from Bacillus amyloliquefaciens An6, and further evaluate their biological activities. An6 lipopeptides were detected by PCR using degenerated primers and MALDI‐TOF‐MS. An6 strain was found to produce surfactin, fengycin, and bacillomycin. Following their purification, the in vitro antioxidant activity of An6 lipopeptides was studied through different assays. The scavenging effect on 1, 1‐diphenyl‐2‐picrylhydrazyl radicals at a dosage of 0.75 mg/mL was 81%. Its reducing power was concentration‐dependant and reached a maximum of 1.07 at 2.5 mg/mL. Moreover, they showed a strong inhibition of β‐carotene bleaching. An6 lipopeptides mixture was also found to display significant antimicrobial activity against several Gram‐positive, Gram‐negative bacteria, and fungal strains. An6 lipopeptides were insensitive to proteolytic enzymes, stable between pH 4.0 and 12.0, and resistant to high temperature. Our results provided enough evidence proving that An6 lipopeptides could be used as functional‐food components.